Burnout among secondary school teachers in Malaysia Sabah - Balan Rathakrishnan; Sanju Geogre; Soon Singh Bikar Singh; Mohammad Rahim Kamaluddin; Mohammad Amin Wani (2020)
The purpose of this study was to identify the relationship between burnout among urban and rural secondary school teachers in Sabah. The study involved 114 teachers currently working in five urban secondary schools in Kota Kinabalu district and five rural secondary schools in Kota Belud district, Sabah. This is a quantitative study in the form of a survey with two (2) questionnaires. Part A contains demographic data while the second part B contains 22 Burnout measurement items using the second version of the Burnout Maslach Inventory (MBI) used to collect instrument data. They were then analyzed using descriptive and t-test to compare two groups. The results of this study indicate that aspects of teacher personalization need to be taken into account as this study clearly shows that there are significant differences between teachers in urban and rural areas. The survey data also showed that rural teachers experienced moderate personalization.